2011
DOI: 10.1177/0748233711416948
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of lycopene and tocopherol against oxidative stress and mammary tumorigenesis induced by 7,12-dimethyl[a]benzanthracene in female rats

Abstract: Breast cancer is one of the most serious problems in oncology. We investigated the antitumor potential of lycopene (Lyco) alone or combined with tocopherol (Lyco + Toco) for 90 days against a single oral dose of (50 mg/kg body weight) 7,12-dimethyl[a]benzanthracene (DMBA)-induced oxidative stress and mammary carcinogenesis in female rats. The treatment protocol started from the day immediately after DMBA administration. Results obtained indicated that there was a significant elevation in the levels of malondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Lycopene has 11 conjugated double bonds and has the most efficient quenching activity among biological carotenoids (15). Previous studies reported that elevated serum lipid peroxide levels induced by 2,7-dimethyl(a)benzanthracene in SD female rats were significantly reduced by a diet supplemented with approximately 50 ppm lycopene for 90 or 120 d, compared with a non-treated group (33,34). In the present study, serum lycopene concentrations in the lycopene intake groups were undetectable by the analytical methods used.…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene has 11 conjugated double bonds and has the most efficient quenching activity among biological carotenoids (15). Previous studies reported that elevated serum lipid peroxide levels induced by 2,7-dimethyl(a)benzanthracene in SD female rats were significantly reduced by a diet supplemented with approximately 50 ppm lycopene for 90 or 120 d, compared with a non-treated group (33,34). In the present study, serum lycopene concentrations in the lycopene intake groups were undetectable by the analytical methods used.…”
Section: Discussionmentioning
confidence: 99%
“…2,24 En este trabajo se utilizó el anión superóxido como marcador de oxidación por ser precursor de otras especies reactivas oxidantes, y por su capacidad de responder a factores ambientales y nutricionales. 4,9,11 Existen datos preclínicos que sugieren actividad antioxidante de los carotenoides no provitamínicos, 25 pero la evidencia en seres humanos no es concluyente. 26 Esto concuerda con la falta de asociación significativa hallada en la presente investigación, entre el consumo de éstos y el nivel de superóxido, al ajustar por edad, estado nutricional y nivel de actividad física.…”
Section: Discussionunclassified
“…Similarly, synergistic inhibition of oxidative stress in a mouse tumor model [40] or inhibition of androgen signaling and PSA secretion by lycopene and tocopherol [41] was determined. In addition, the synergistic effect of a TNC and carnosic acid (from rosemary) has recently been observed on inhibition of UVB-induced IL6 secretion in keratinocytes as compared to the single interventions (Calniquer et al, unpublished data).…”
Section: Resultsmentioning
confidence: 99%